Insecticidal and repellent activity of the essential oil of Cinnamomum camphora var. linaloolifera Y. Fujita (Ho-Sho) and Cinnamomum camphora (L.) J Presl. var. hosyo (Hon-Sho) on Sitophilus zeamaisMots. (Coleoptera, Curculionedae) - R.L. CANSIAN; V. ASTOLFI; R.I. CARDOSO; N. PAROUL; S.S. ROMAN; A.A. MIELNICZKI-PEREIRA; G.F. PAULETTI; A. J. MOSSI (Universidade Estadual Paulista, 2015)
ABSTRACT The aim of this work was to evaluate the insecticidal and repellency activity of the essential oil of Cinnamomum camphora var. linaloolifera Y. Fujita (Ho-Sho) and Cinnamomumcamphora (L.) J Presl.var. hosyo (Hon-Sho), against the Sitophilus zeamais in maize grains. The essential oils were obtained by hydrodistillation and analyzed by GC-MS.The insecticidal activity was determined by the toxicity of different concentrations of essential oils during 24 hours of contact with the insects, in the absence of feed substrate. The Bioassays of repellency were conducted with lethal doses (LD50,LD25,and LD12.5) obtained from insecticidal bioassay. In order to compare the treatments the preference index (PI) was employed. The analysis of the essential oils of Cinnamomum camphora leaves indicated 68% of camphor and 9% of linalool for the variation Hon-Sho and 95% of linalool to the variation Ho-Sho. The variation Ho-Sho presented greatest insecticidal activity than the variation Hon-Sho against the Sitophiluszeamais, with LD50 of 0.35 μL/cm2, whereas in the variation Hon-Sho the ratewas 0.48 μL/cm2. However, considering only the concentrations of linalool and camphor of Ho-Sho and Hon-Sho, the lethal doses' evaluation of these compounds were similar. The values of the preference index ranged from -0.3 to -0.8 for thevariation Ho-Sho and -0.2 to -0.7 for the variation Hon-Sho. The essential oils evaluated in this work showed repellent activity against Sitophiluszeamais in vitro and in trials performed in mini-silos.